Modelling workplace spirituality and teaching effectiveness for academician in Malaysia - Mat, Norazuwa; Romli, Ruslan; Mat, Norsiah; Mohd Noor, Nor Azila (The Social Sciences Research Society, 2012)
Teaching effectiveness is a complex area of study without supported by an extensive body of empirical research.Developing effective behaviors is a part of every academician in Malaysia. With the surge in public demand for accountability in higher education and the growing concern for quality of university teaching, evaluating teaching effectiveness is very important function. Workplace spirituality is among the important factors that pose a strong influence on teaching effectiveness.In teaching effectiveness, the concern of workplace spirituality relate to inner life, meaningful work, and sense of community.This paper examines the effect of workplace spirituality on teaching effectiveness for academician in public universities in Malaysia.Structured Equation Modeling (SEM) was conducted to test the model. Results were then discussed.